2015
DOI: 10.1111/febs.13250
|View full text |Cite
|
Sign up to set email alerts
|

Roles of p38α mitogen‐activated protein kinase in mouse models of inflammatory diseases and cancer

Abstract: The p38α mitogen‐activated protein kinase pathway not only regulates the production of inflammatory mediators, but also controls processes related to tissue homeostasis, such as cell proliferation, differentiation and survival, which are often disrupted during malignant transformation. The versatility of this signaling pathway allows for the regulation of many specific functions depending on the cell type and context. Here, we discuss mouse models that have been used to identify in vivo functions of p38α signa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
100
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(110 citation statements)
references
References 122 publications
4
100
0
1
Order By: Relevance
“…P38MAPK and ERK1/2 may regulate oxidative stress and inflammatory responses [34, 35]. It is known that many I/R injury models elicited the activation of p38MAPK and ERK1/2 pathways [3638].…”
Section: Discussionmentioning
confidence: 99%
“…P38MAPK and ERK1/2 may regulate oxidative stress and inflammatory responses [34, 35]. It is known that many I/R injury models elicited the activation of p38MAPK and ERK1/2 pathways [3638].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the Western diet group did not significantly result in increased p38 activation as exhibited by the AIN-76A Mod, 6% SF, and 12% SF groups. The IL-6-STAT3 pathway has been shown to be a key regulator of colon cancer development (46), and it has recently been shown that p38 is required for cancer cell survival (20), and can serve as an activator of STAT3 (21). Thus, it is not surprising that the decreased p38 activity was associated with less STAT3 activation and proliferation in the Western diet group.…”
Section: Discussionmentioning
confidence: 99%
“…2, 28 Since p38 MAPK plays a critical role in inducing inflammation in multiple tissue types, 19, 20, 32 we sought to evaluate whether inhibition of p38 MAPK could regulate the expression of several genes known to be regulated by p38 MAPK that are involved in inflammation in skeletal muscle tissue. IL1β and IL6 are potent proinflammatory cytokines known to direct atrophy and collagen production, 1, 12 and IL10 is an antiinflammatory gene that can protect against atrophy and fibrosis in skeletal muscle tissue.…”
Section: Discussionmentioning
confidence: 99%